Intensitas Penilaian Portofolio dalam Pembelajaran Matematika pada Pokok Bahasan Lingkaran Siswa Kelas VIII SMP N 1 Kartasura Tahun Ajaran 2016/2017 - Setyawan, Bambang; , Dr. Sumardi, M.Si (2017)
This research was conducted with the aim of describing the steps of assessment, implementation and obstacles to the process of assessment of portfolio assessment in mathematics in junior 1 Katasura. This type of research is qualitative descriptive. Subjects of this study were 30 students of class VIII 8 G SMP N 1 Kartasura. Data collection techniques in this study using the test method, observation, and interviews, document. Data validation was done by triangulation method, by comparing the test results with interview. Data analysis techniques carried out in three stages: data reduction, data presentation, and data verification and conclusion. Rate Indicator is divided into 4 test, structured tasks, notes the daily behavior and report activities outside of school. Results showed the indicators used in the implementation include tests, tasks structured, daily behavior charts, with this indicator teachers can view student progress over time and sustained. The problem faced in this assessment are time management, task structured tasks usually not authentic student work alone, the number of students is too much. Keywords: intensity, portfolio assessment, circle